2016
DOI: 10.1016/j.eurpsy.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel psychoactive substances: An investigation of temporal trends in social media and electronic health records

Abstract: BackgroundPublic health monitoring is commonly undertaken in social media but has never been combined with data analysis from electronic health records. This study aimed to investigate the relationship between the emergence of novel psychoactive substances (NPS) in social media and their appearance in a large mental health database.MethodsInsufficient numbers of mentions of other NPS in case records meant that the study focused on mephedrone. Data were extracted on the number of mephedrone (i) references in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The separate codes for each search and extraction can be found at github.com/ leondz/medtermfilter. Another investigation under PHEME using a similar methodology and examining novel psychoactive substances in the EHR and online data sources has also been described elsewhere 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The separate codes for each search and extraction can be found at github.com/ leondz/medtermfilter. Another investigation under PHEME using a similar methodology and examining novel psychoactive substances in the EHR and online data sources has also been described elsewhere 35 .…”
Section: Discussionmentioning
confidence: 99%
“…All the users, indeed, can be part of a #highsociety, allowing them to share their #proudstoners daily states of mind. Very recently, epidemiologists and linguistic scientists used Twitter to test the feasibility of producing a fully-automated “drug term discovery” system capable of tracking emerging NPS terms in real time [ 49 ], which confirms that data collected on Twitter may be used to explore trends in NPS selling and use [ 50 ]. Along with other cyber drug communities (e.g., blogs, drug fora, Facebook), Twitter allowed the identification and characterization of a new generation of NPS users, the so-called “e-psychonauts”, that considered themselves as psychedelic researchers, mind navigators, or chemicals experimenters [ 51 ].…”
Section: Social Network and Smartphone Appsmentioning
confidence: 92%
“…Finally, we reported training and testing on the in-domain data only and showed that the results are substantially lower compared to the case when the training data is augmented with the out-domain data. Our rumour stance classifier applied to new, obscure domains with shortage of training data has numerous applications that we aim to explore in the near future, such as rumours around bullying and suicide [10], or disputed perceptions around psychoactive substances [11]. Further improving our classifier, in future work we also aim to perform a more detailed analysis underpinning the reasons for the performance drop.…”
Section: Discussionmentioning
confidence: 99%